Ali Topan Lubis PENERAPAN KONSEP MASLAHA DALAM KEGIATAN EKONOMI ISLAM - ali topan lubis (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2022)
In Islamic principles, everything related to Islamic teachings, whether related to faith (aqidah), worship ('worship) or human relations (muamalah) in principle aims to ensure the safety of humaIn Islamic principles, everything related to Islamic teachings, whether related to faith (aqidah), worship ('worship) or human relations (muamalah) in principle aims to ensure the safety of humans themselves in the world and the hereafter, then maslahah is a concept most important in economic development fiber Maslahah principles in the economic field serve as a reference and guideline in order to achieve maqashid sharia. In Islamic teachings, implementing sharia law is a way to realize the maslahah itself. The implementation of mashlahah in economic practice must be seen from the various activities of the people in carrying out economic practices that are developing continuously and innovatively in today's modern times, such as in market mechanisms, the establishment of hisbah institutions productive divine taxes (zakat), the existence of Islamic financial institutions, and so on.ns themselves in the world and the hereafter, then maslahah is a concept most important in economic development fiber Maslahah principles in the economic field serve as a reference and guideline in order to achieve maqashid sharia. In Islamic teachings, implementing sharia law is a way to realize the maslahah itself. The implementation of mashlahah in economic practice must be seen from the various activities of the people in carrying out economic practices that are developing continuously and innovatively in today's modern times, such as in market mechanisms, the establishment of hisbah institutions productive divine taxes (zakat), the existence of Islamic financial institutions, and so on.